A qualitative study of the views of health and social care decision-makers on the role of wellbeing in resource allocation decisions in the UK - Tessa Peasgood; Jill Carlton; John Brazier (Economies, 2019)
There has been growing international interest in the role that wellbeing measures could play within policy making in health and social care. This project explored the opinions of a sample of UK decision-makers on the relevance of wellbeing and subjective wellbeing (by which we mean good and bad feelings or overall evaluations of life, such as life satisfaction) for resource allocation decisions within health and social care. Through these discussions we draw out the perceived advantages and the potential concerns that decision-makers have about broadening out to wellbeing and subjective wellbeing rather than just measuring health. Three focus groups were conducted: with members of the National Institute for Health and Care Excellence (NICE) Citizen's Council, with a Health and Wellbeing Board at a Local Authority and with Public Health England. In addition, eleven semi-structured interviews were held with staff from NHS England and members of a range of NICE committees. We identified a range of opinions about the role of wellbeing and a broadly held view that there was a need for improved consideration of broader quality of life outcomes. We also identified considerable caution in relation to the use of subjective wellbeing.
Keywords: I31; I18; 330; qualitative; subjective wellbeing; resource allocation; QALYs; health; happiness; UK; National Institute for Health and Care Excellence (NICE)